Preparation method of CoFe@MXene / carbon aerogel composite material
By preparing CoFe@MXene/carbon aerogel composite material, using three-dimensional conductive network and magnetic filler, the problem of low electromagnetic shielding performance of existing composite materials is solved, and high-performance electromagnetic shielding and absorption effects are achieved. The preparation method is simple and cost-effective.
Patent Information
- Application Number
- CN202111041252.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-09-06
AI Technical Summary
The existing composite materials have low electromagnetic shielding performance and poor electromagnetic wave absorption capacity, making it difficult to effectively solve the problem of electromagnetic wave pollution.
The preparation method of CoFe@MXene/carbon aerogel composite was used to prepare a small layer of MXene powder by etching the Ti3AlC2 precursor by LiF-HCl, and CoFe2O4@MXene powder was prepared by hydrothermal method, and CoFe2O4@MXene/cellulose aerogel was prepared using cellulose. Finally, the CoFe@MXene/carbon aerogel composite was obtained by carbonization treatment.
Through the combination of a highly interconnected three-dimensional conductive network and magnetic filler, the electromagnetic shielding performance and electromagnetic wave absorption capacity of the composite material are improved, and the high-performance electromagnetic shielding effect is achieved. At the same time, the preparation method is simple and cost-effective.
Smart Images

Figure CN113873859B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a method for preparing a CoFe@MXene / carbon aerogel composite material. Background Art
[0002] With the widespread application of electromagnetic wave technology in human daily life and the development trend of miniaturization and integration of electronic devices, while bringing convenience to human life, the electromagnetic wave pollution generated has seriously affected the normal operation of precision instruments and even posed a certain threat to human health. Although traditional electromagnetic shielding materials based on impedance mismatch have high shielding effectiveness, serious electromagnetic wave secondary pollution makes the electromagnetic environment more complicated. Therefore, designing electromagnetic shielding materials with both high-efficiency electromagnetic shielding performance and strong electromagnetic wave absorption ability is of great significance to solving this problem.
[0003] A large number of studies have found that introducing magnetic components into composite materials to provide magnetic loss and construct a three-dimensional conductive network is a key strategy to alleviate the impedance mismatch between the material and free space, which can allow more electromagnetic waves to enter the interior of the composite material and enhance the multiple reflections and scattering inside the material. x (MXene) as a typical magnetic material and conductive filler has been widely used in shielding materials. However, due to its weak gelation ability, MXene is difficult to form a strong three-dimensional skeleton. In recent years, biomass carbon materials used for shielding have attracted widespread attention due to their low cost and renewability. Cellulose is one of the almost inexhaustible low-cost biomass resources on the earth. Because it contains a large number of hydrogen bonds, it is considered to be an advanced candidate raw material for building a three-dimensional framework structure. Cellulose provides a platform for MXene and CoFe to form a strong three-dimensional skeleton. In addition, studies have shown that the three-dimensional highly connected conductive network of the composite material plays a vital role in its conductivity and electromagnetic shielding effect. Using aerogel composed of cellulose as a precursor, it can be converted into a three-dimensional continuous porous conductive skeleton through a simple pyrolysis process without destroying its structure. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a CoFe@MXene / carbon aerogel composite material, which solves the problems of low electromagnetic shielding performance and poor electromagnetic wave absorption capacity of the composite material in the prior art.
[0005] The technical solution adopted by the present invention is a method for preparing a CoFe@MXene / carbon aerogel composite material, which is specifically implemented according to the following steps:
[0006] Step 1, preparing a few-layer MXene powder by etching Ti3AlC2 precursor with LiF-HCl;
[0007] Step 2, preparing CoFe2O4@MXene powder by hydrothermal method;
[0008] Step 3, preparing CoFe2O4@MXene / cellulose aerogel using CoFe2O4@MXene powder and cellulose;
[0009] Step 4, placing the CoFe2O4@MXene / cellulose aerogel obtained in step 3 into a tubular furnace for carbonization treatment to obtain a CoFe@MXene / carbon aerogel composite material.
[0010] The present invention is also characterized in that:
[0011] In step 1, the specific steps are as follows:
[0012] Step 1.1, LiF and HCl are fully mixed, and then MAX phase precursor powder is slowly added under ice bath conditions to obtain a mixture;
[0013] The mass ratio of LiF, HCl and MAX phase precursor powder is 1:20:1;
[0014] Step 1.2, stirring the mixture at 35 °C for 24 h to obtain Ti3C2T x The suspension was then repeatedly centrifuged and washed with deionized water until the pH of the solution was 7 to obtain Ti3C2T x Sediment;
[0015] Step 1.3, Ti3C2T x The precipitate was dispersed in deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the mixture was centrifuged at 3500 r / min for 15 min, and the cycle was repeated several times. The supernatant was collected to obtain a few-layer MXene dispersion.
[0016] Step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C, and then freeze-dried using a freeze dryer to obtain a few-layer MXene powder.
[0017] In step 2, specifically: PVP is dissolved in deionized water under magnetic stirring. After complete dissolution, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and few-layer MXene powder are added to the solution, ultrasonically dispersed for 30 minutes, urea is added, and mixed evenly. Then, the mixed solution is transferred to a high-pressure reactor, sealed, and hydrothermally reacted at 180°C for 12 hours. Naturally cooled to room temperature, the precipitate is collected, washed and dried to obtain CoFe2O4@MXene powder.
[0018] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and deionized water is 0.15: 0.135~0.404: 0.097~0.145: 0.7047~0.548: 0.12: 60.
[0019] In step 3, specifically:
[0020] Step 3.1, add NaOH and urea to deionized water, stir for 15 minutes to obtain a mixed solution, and then place the mixed solution in a refrigerator for refrigeration; then add cellulose powder, stir evenly, freeze the solution in a refrigerator, thaw naturally, add CoFe2O4@MXene powder, disperse by ultrasonic, and then freeze at -26°C for 12 hours. After natural thawing, add MBA and stir evenly;
[0021] Step 3.2, pour the mixed solution obtained after step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, then wash it with deionized water until it is neutral, freeze it at -26°C for 12h, and finally freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel.
[0022] In step 3.1, the refrigeration temperature is -12°C, and the refrigeration time is 12 hours; the freezing temperature is -26°C, and the freezing time is 24 hours.
[0023] In step 3.1, the mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA and deionized water is 7:12:0.1458:2.43:2.34:81.
[0024] In step 4, the carbonization conditions are as follows: nitrogen is introduced at a rate of 50 to 100 mL / s, the temperature is first raised to 300°C at a rate of 3°C / min and kept for 1 h, then the temperature is raised to 800°C to 1200°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0025] The beneficial effect of the present invention is that by designing a highly interconnected three-dimensional conductive network and introducing magnetic fillers to provide magnetic loss, a high-performance electromagnetic shielding composite material dominated by an absorption mechanism is prepared; at the same time, the preparation method is simple and easy, the production cost is low, and mass production is possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the total electromagnetic shielding effectiveness (SE) of CoFe@MXene / carbon aerogel at different CoFe contents in the method of the present invention. T )picture;
[0027] Figure 2 The SE of CoFe@MXene / carbon aerogel at different CoFe contents in the method of the present invention is R , SE A picture;
[0028] Figure 3 is the total electromagnetic shielding effectiveness (SE) of CoFe@MXene / carbon aerogel at different carbonization temperatures in the method of the present invention. T )picture;
[0029] Figure 4 is the SE of CoFe@MXene / carbon aerogel at different carbonization temperatures in the method of the present invention. R , SE A picture. DETAILED DESCRIPTION
[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0032] Step 1: Prepare a few-layer MXene powder by etching Ti3AlC2 precursor with LiF-HCl; the specific steps are as follows:
[0033] Step 1.1, LiF and HCl are fully mixed, and then MAX phase precursor powder is slowly added under ice bath conditions to obtain a mixture;
[0034] The mass ratio of LiF, HCl and MAX phase precursor powder is 1:20:1;
[0035] The manufacturer of the MAX phase precursor powder (Ti3AlC2 powder) is Beijing Fusiman Technology Co., Ltd. The purity of the MAX phase precursor powder is 98%, and the particle size of the MAX phase precursor powder is 200 meshes.
[0036] Step 1.2, stirring the mixture at 35 °C for 24 h to obtain Ti3C2T x The suspension was then repeatedly centrifuged and washed with deionized water until the pH of the solution was 7 to obtain Ti3C2T x Sediment;
[0037] During centrifugal washing, the centrifugal speed was 3500r / min;
[0038] Step 1.3, Ti3C2T xThe precipitate was dispersed in deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the mixture was centrifuged at 3500 r / min for 15 min, and the cycle was repeated several times. The supernatant was collected to obtain a few-layer MXene dispersion.
[0039] Step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C, and then freeze-dried using a freeze dryer to obtain a few-layer MXene powder;
[0040] Step 2, preparing CoFe2O4@MXene powders with different magnetic material contents by a hydrothermal method;
[0041] Specifically, polyvinyl pyrrolidone (PVP) was dissolved in deionized water under magnetic stirring. After it was completely dissolved, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and few-layer MXene powder were added to the solution, ultrasonically dispersed for 30 minutes, urea was added, and mixed evenly. The mixed solution was then transferred to a high-pressure reactor, sealed, and hydrothermally reacted at 180°C for 12 hours. The mixture was naturally cooled to room temperature, and the precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder.
[0042] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and deionized water is 0.15: 0.135~0.404: 0.097~0.145: 0.7047~0.548: 0.12: 60;
[0043] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel; specifically:
[0044] Step 3.1, add NaOH and urea to deionized water, stir for 15 minutes to obtain a mixed solution, and then place the mixed solution in a refrigerator for refrigeration; then add cellulose powder, stir evenly, freeze the solution in a refrigerator, thaw naturally, add CoFe2O4@MXene powder, disperse by ultrasonic, and then freeze at -26°C for 12 hours. After natural thawing, add MBA and stir evenly;
[0045] The refrigeration temperature is -12℃ and the refrigeration time is 12h. The freezing temperature is -26℃ and the freezing time is 24h.
[0046] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and deionized water is 7:12:0.1458:2.43:2.34:81;
[0047] Step 3.2, pour the mixed solution obtained in step 3.1 into a mold of a six-well cell culture plate, let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, then wash it with deionized water to neutrality, freeze it at -26°C for 12h, and finally freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0048] Step 4, placing the CoFe2O4@MXene / cellulose aerogel obtained in step 3 into a tubular furnace for carbonization treatment to obtain a CoFe@MXene / carbon aerogel composite material.
[0049] The specific carbonization conditions are as follows: nitrogen is introduced at a rate of 50-100 mL / s, the temperature is first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 800°C-1200°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0050] Example 1
[0051] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0052] Step 1: Prepare few-layer Ti3C2T by etching Ti3AlC2 precursor with LiF-HCl x MXene powder, the specific steps are as follows:
[0053] Step 1.1, 2 g LiF was thoroughly mixed with 40 mL 9 mol / L HCl, and then 2 g MAX phase precursor powder was slowly added under ice bath conditions;
[0054] Step 1.2, stirring the above mixture at 35 °C for 24 hours to obtain Ti3C2T x The suspension was washed repeatedly with deionized water until the pH was 7 and centrifuged at 3500 r / min;
[0055] Step 1.3, Ti3C2T x The precipitate was dispersed in 100 ml of deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the precipitate was centrifuged at 3500 r / min for 15 min for several cycles. The supernatant was collected to obtain a MXene dispersion.
[0056] In step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C for 12 hours and then freeze-dried for 48 hours to obtain the few-layer MXene powder.
[0057] Step 2: Prepare CoFe2O4@MXene powder by hydrothermal method. The specific steps are as follows:
[0058] Step 2.1, under magnetic stirring, 0.15 g of polyvinyl pyrrolidone (PVP) was dissolved in 60 mL of deionized water. After complete dissolution, 0.135 g of Fe(NO3)3·9H2O, 0.097 g of Co(NO3)2·6H2O and 0.7047 g of few-layer MXene powder were added to the solution mixture, ultrasonically dispersed for 30 minutes, and 0.12 g of urea was added and mixed evenly;
[0059] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and water is 0.15:0.135:0.097:0.7047:0.12:60.
[0060] Step 2.2, the mixture was transferred into an autoclave, sealed, maintained at 180°C for 12 h, and then cooled naturally to room temperature. The precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder with a CoFe2O4 loading of 10 wt% in MXene.
[0061] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel, the specific steps are as follows:
[0062] Step 3.1, add NaOH and urea powder to deionized water, stir for 15 minutes to make them evenly dispersed, place the mixed solution in a -12°C refrigerator for 12 hours, take it out, add 2.43g cellulose powder, and stir it evenly with a glass rod; place the above solution in a -26°C refrigerator for 24 hours, take it out, thaw it naturally at room temperature, add the prepared CoFe2O4@MXene powder, ultrasonically disperse it, freeze it again for 12 hours, add 2.34g N,N-methylenebisacrylamide (MBA) after natural thawing, and stir it vigorously with a glass rod to make it evenly dispersed;
[0063] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and water is 7:12:0.1458:2.43:2.34:81;
[0064] Step 3.2, pour the mixed solution obtained in step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, wash it with deionized water to neutrality, freeze it at -26°C for 12h, and freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0065] Step 4: The aerogel obtained in step 3 is used as a precursor and placed in a tubular furnace for carbonization treatment to prepare a CoFe@MXene / carbon aerogel composite material.
[0066] The carbonization conditions were as follows: nitrogen was introduced at a rate of 50 mL / s, the temperature was first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 800°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0067] Compared with commercial electromagnetic shielding materials (20 dB), the electromagnetic shielding effectiveness of the CoFe@MXene / carbon aerogel composite material prepared in Example 1 is 38.6 dB, which is a corresponding increase of 93%.
[0068] Example 2
[0069] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0070] Step 1: Prepare few-layer Ti3C2T by etching Ti3AlC2 precursor with LiF-HCl x MXene powder, the specific steps are as follows:
[0071] Step 1.1, 2 g LiF was thoroughly mixed with 40 mL 9 mol / L HCl, and then 2 g MAX phase precursor powder was slowly added under ice bath conditions;
[0072] Step 1.2, stirring the above mixture at 35 °C for 24 hours to obtain Ti3C2T x The suspension was washed repeatedly with deionized water until the pH was 7 and centrifuged at 3500 r / min;
[0073] Step 1.3, Ti3C2T x The precipitate was dispersed in 100 ml of deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the precipitate was centrifuged at 3500 r / min for 15 min for several cycles. The supernatant was collected to obtain a MXene dispersion.
[0074] In step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C for 12 hours and then freeze-dried for 48 hours to obtain the few-layer MXene powder.
[0075] Step 2: Prepare CoFe2O4@MXene powders with different magnetic material contents by hydrothermal method. The specific steps are as follows:
[0076] Step 2.1, under magnetic stirring, 0.15 g of polyvinyl pyrrolidone (PVP) was dissolved in 60 mL of deionized water. After complete dissolution, 0.27 g of Fe(NO3)3·9H2O, 0.194 g of Co(NO3)2·6H2O and 0.6264 g of few-layer MXene powder were added to the solution mixture, ultrasonically dispersed for 30 minutes, 0.12 g of urea was added, and mixed evenly;
[0077] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and water is 0.15:0.27:0.194:0.6264:0.12:60.
[0078] Step 2.2, the mixture was transferred into an autoclave, sealed, maintained at 180°C for 12 h, and then cooled naturally to room temperature. The precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder with a CoFe2O4 loading of 20 wt% in MXene.
[0079] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel, the specific steps are as follows:
[0080] Step 3.1, add NaOH and urea powder to deionized water, stir for 15 minutes to make them evenly dispersed, place the mixed solution in a -12°C refrigerator for 12 hours, take it out, add 2.43g cellulose powder, and stir it evenly with a glass rod; place the above solution in a -26°C refrigerator for 24 hours, take it out, thaw it naturally at room temperature, add the prepared CoFe2O4@MXene powder, ultrasonically disperse it, freeze it again for 12 hours, add 2.34g N,N-methylenebisacrylamide (MBA) after natural thawing, and stir it vigorously with a glass rod to make it evenly dispersed;
[0081] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and water is 7:12:0.1458:2.43:2.34:81;
[0082] Step 3.2, pour the mixed solution obtained in step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, wash it with deionized water to neutrality, freeze it at -26°C for 12h, and freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0083] Step 4: The aerogel obtained in step 3 is used as a precursor and placed in a tubular furnace for carbonization treatment to prepare a CoFe@MXene / carbon aerogel composite material.
[0084] The carbonization conditions were as follows: nitrogen was introduced at a rate of 50-100 mL / s, the temperature was first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 800°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0085] Compared with commercial electromagnetic shielding materials (20 dB), the electromagnetic shielding effectiveness of the CoFe@MXene / carbon aerogel composite material prepared in Example 2 is 47.2 dB, which is a corresponding increase of 136%.
[0086] Example 3
[0087] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0088] Step 1: Prepare few-layer Ti3C2T by etching Ti3AlC2 precursor with LiF-HCl x MXene powder, the specific steps are as follows:
[0089] Step 1.1, 2 g LiF was thoroughly mixed with 40 mL 9 mol / L HCl, and then 2 g MAX phase precursor powder was slowly added under ice bath conditions;
[0090] Step 1.2, stirring the above mixture at 35 °C for 24 hours to obtain Ti3C2T x The suspension was washed repeatedly with deionized water until the pH was 7 and centrifuged at 3500 r / min;
[0091] Step 1.3, Ti3C2T x The precipitate was dispersed in 100 ml of deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the precipitate was centrifuged at 3500 r / min for 15 min for several cycles. The supernatant was collected to obtain a MXene dispersion.
[0092] In step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C for 12 hours and then freeze-dried for 48 hours to obtain the few-layer MXene powder.
[0093] Step 2: Prepare CoFe2O4@MXene powders with different magnetic material contents by hydrothermal method. The specific steps are as follows:
[0094] Step 2.1, under magnetic stirring, 0.15 g of polyvinyl pyrrolidone (PVP) was dissolved in 60 mL of deionized water. After complete dissolution, 0.27 g of Fe(NO3)3·9H2O, 0.194 g of Co(NO3)2·6H2O and 0.6264 g of few-layer MXene powder were added to the solution mixture, ultrasonically dispersed for 30 minutes, 0.12 g of urea was added, and mixed evenly;
[0095] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and water is 0.15:0.404:0.145:0.548:0.12:60.
[0096] Step 2.2, the mixture was transferred into an autoclave, sealed, maintained at 180°C for 12 h, and then cooled naturally to room temperature. The precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder with a CoFe2O4 loading of 30 wt% in MXene.
[0097] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel, the specific steps are as follows:
[0098] Step 3.1, add NaOH and urea powder to deionized water, stir for 15 minutes to make them evenly dispersed, place the mixed solution in a -12°C refrigerator for 12 hours, take it out, add 2.43g cellulose powder, and stir it evenly with a glass rod; place the above solution in a -26°C refrigerator for 24 hours, take it out, thaw it naturally at room temperature, add the prepared CoFe2O4@MXene powder, ultrasonically disperse it, freeze it again for 12 hours, add 2.34g N,N-methylenebisacrylamide (MBA) after natural thawing, and stir it vigorously with a glass rod to make it evenly dispersed;
[0099] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and water is 7:12:0.1458:2.43:2.34:81;
[0100] Step 3.2, pour the mixed solution obtained in step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, wash it with deionized water to neutrality, freeze it at -26°C for 12h, and freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0101] Step 4: The aerogel obtained in step 3 is used as a precursor and placed in a tubular furnace for carbonization treatment to prepare a CoFe@MXene / carbon aerogel composite material.
[0102] The carbonization conditions were as follows: nitrogen was introduced at a rate of 50-100 mL / s, the temperature was first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 800°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0103] Compared with commercial electromagnetic shielding materials (20 dB), the electromagnetic shielding effectiveness of the CoFe@MXene / carbon aerogel composite material prepared in Example 3 is 51.5 dB, which is a corresponding increase of 157.5%.
[0104] Example 4
[0105] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0106] Step 1: Prepare few-layer Ti3C2T by etching Ti3AlC2 precursor with LiF-HCl x MXene powder, the specific steps are as follows:
[0107] Step 1.1, 2 g LiF was thoroughly mixed with 40 mL 9 mol / L HCl, and then 2 g MAX phase precursor powder was slowly added under ice bath conditions;
[0108] Step 1.2, stirring the above mixture at 35 °C for 24 hours to obtain Ti3C2T x The suspension was washed repeatedly with deionized water until the pH was 7 and centrifuged at 3500 r / min;
[0109] Step 1.3, Ti3C2T x The precipitate was dispersed in 100 ml of deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the precipitate was centrifuged at 3500 r / min for 15 min for several cycles. The supernatant was collected to obtain a MXene dispersion.
[0110] In step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C for 12 hours and then freeze-dried for 48 hours to obtain the few-layer MXene powder.
[0111] Step 2: Prepare CoFe2O4@MXene powders with different magnetic material contents by hydrothermal method. The specific steps are as follows:
[0112] Step 2.1, under magnetic stirring, 0.15 g of polyvinyl pyrrolidone (PVP) was dissolved in 60 mL of deionized water. After complete dissolution, 0.27 g of Fe(NO3)3·9H2O, 0.194 g of Co(NO3)2·6H2O and 0.6264 g of few-layer MXene powder were added to the solution mixture, ultrasonically dispersed for 30 minutes, 0.12 g of urea was added, and mixed evenly;
[0113] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and water is 0.15:0.404:0.145:0.548:0.12:60.
[0114] Step 2.2, the mixture was transferred into an autoclave, sealed, maintained at 180°C for 12 h, and then cooled naturally to room temperature. The precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder with a CoFe2O4 loading of 30 wt% in MXene.
[0115] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel, the specific steps are as follows:
[0116] Step 3.1, add NaOH and urea powder to deionized water, stir for 15 minutes to make them evenly dispersed, place the mixed solution in a -12°C refrigerator for 12 hours, take it out, add 2.43g cellulose powder, and stir it evenly with a glass rod; place the above solution in a -26°C refrigerator for 24 hours, take it out, thaw it naturally at room temperature, add the prepared CoFe2O4@MXene powder, ultrasonically disperse it, freeze it again for 12 hours, add 2.34g N,N-methylenebisacrylamide (MBA) after natural thawing, and stir it vigorously with a glass rod to make it evenly dispersed;
[0117] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and water is 7:12:0.1458:2.43:2.34:81;
[0118] Step 3.2, pour the mixed solution obtained in step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, wash it with deionized water to neutrality, freeze it at -26°C for 12h, and freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0119] Step 4: The aerogel obtained in step 3 is used as a precursor and placed in a tubular furnace for carbonization treatment to prepare a CoFe@MXene / carbon aerogel composite material.
[0120] The carbonization conditions were as follows: nitrogen was introduced at a rate of 50-100 mL / s, the temperature was first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 1000°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0121] Compared with commercial electromagnetic shielding materials (20 dB), the electromagnetic shielding effectiveness of the CoFe@MXene / carbon aerogel composite material prepared in Example 4 is 62.9 dB, which is a corresponding increase of 214.5%.
[0122] Example 5
[0123] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention is specifically implemented according to the following steps:
[0124] Step 1: Prepare few-layer Ti3C2T by etching Ti3AlC2 precursor with LiF-HCl x MXene powder, the specific steps are as follows:
[0125] Step 1.1, 2 g LiF was thoroughly mixed with 40 mL 9 mol / L HCl, and then 2 g MAX phase precursor powder was slowly added under ice bath conditions;
[0126] Step 1.2, stirring the above mixture at 35 °C for 24 hours to obtain Ti3C2T x The suspension was washed repeatedly with deionized water until the pH was 7 and centrifuged at 3500 r / min;
[0127] Step 1.3, Ti3C2T x The precipitate was dispersed in 100 ml of deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the precipitate was centrifuged at 3500 r / min for 15 min for several cycles. The supernatant was collected to obtain a MXene dispersion.
[0128] In step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C for 12 hours and then freeze-dried for 48 hours to obtain the few-layer MXene powder.
[0129] Step 2: Prepare CoFe2O4@MXene powders with different magnetic material contents by hydrothermal method. The specific steps are as follows:
[0130] Step 2.1, under magnetic stirring, 0.15 g of polyvinyl pyrrolidone (PVP) was dissolved in 60 mL of deionized water. After complete dissolution, 0.27 g of Fe(NO3)3·9H2O, 0.194 g of Co(NO3)2·6H2O and 0.6264 g of few-layer MXene powder were added to the solution mixture, ultrasonically dispersed for 30 minutes, 0.12 g of urea was added, and mixed evenly;
[0131] The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and water is 0.15:0.404:0.145:0.548:0.12:60.
[0132] Step 2.2, the mixture was transferred into an autoclave, sealed, maintained at 180°C for 12 h, and then cooled naturally to room temperature. The precipitate was collected, washed, and dried to obtain CoFe2O4@MXene powder with a CoFe2O4 loading of 30 wt% in MXene.
[0133] Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel, the specific steps are as follows:
[0134] Step 3.1, add NaOH and urea powder to deionized water, stir for 15 minutes to make them evenly dispersed, place the mixed solution in a -12°C refrigerator for 12 hours, take it out, add 2.43g cellulose powder, and stir it evenly with a glass rod; place the above solution in a -26°C refrigerator for 24 hours, take it out, thaw it naturally at room temperature, add the prepared CoFe2O4@MXene powder, ultrasonically disperse it, freeze it again for 12 hours, add 2.34g N,N-methylenebisacrylamide (MBA) after natural thawing, and stir it vigorously with a glass rod to make it evenly dispersed;
[0135] The mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA, and water is 7:12:0.1458:2.43:2.34:81;
[0136] Step 3.2, pour the mixed solution obtained in step 3.1 into the mold of a six-well cell culture plate and let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, wash it with deionized water to neutrality, freeze it at -26°C for 12h, and freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel;
[0137] Step 4: The aerogel obtained in step 3 is used as a precursor and placed in a tubular furnace for carbonization treatment to prepare a CoFe@MXene / carbon aerogel composite material.
[0138] The carbonization conditions were as follows: nitrogen was introduced at a rate of 50-100 mL / s, the temperature was first raised to 300°C at a rate of 3°C / min and kept for 1 h, then raised to 1200°C at a rate of 5°C / min and kept for 2 h, and then cooled to room temperature.
[0139] Compared with commercial electromagnetic shielding materials (20 dB), the electromagnetic shielding effectiveness of the CoFe@MXene / carbon aerogel composite material prepared in Example 5 is 75.5 dB, which is a corresponding increase of 277.5%.
[0140] SE of CoFe@MXene / carbon aerogel composites with different CoFe contents prepared by the present invention T Figure, such as Figure 1 As shown in Figure 2, as the content of CoFe in MXene increases, the shielding effectiveness also increases; at different carbonization temperatures, the SE of CoFe@MXene / carbon aerogel T Figure, such as Figure 3 As shown, as the carbonization temperature increases, the shielding effectiveness increases. Figure 2 and Figure 4 The SE of the composites at different magnetic filler contents and carbonization temperatures are R , SE A From the figure, it can be clearly seen that the shielding mechanism is mainly absorption, and the reflection is extremely small, all <3dB. The CoFe@MXene / carbon aerogel composite material glue exhibits excellent electromagnetic shielding performance.
[0141] The mechanism of the method of the present invention is: using the CoFe@MXene / carbon aerogel composite material with a magnetic three-dimensional network structure, when the electromagnetic wave enters, the incident electromagnetic wave and the surface are optimized for impedance matching due to the magnetic component and the porous structure, so that the electromagnetic wave is easy to enter the interior of the material. Subsequently, the incident electromagnetic wave attenuates the incident wave through multiple reflections and scattering in the porous structure. In addition, CoFe provides magnetic loss, which improves the loss capacity of the electromagnetic wave. In addition, due to the addition of CoFe and MXene in the composite material, a large number of effective interfaces are obtained, which triggers interface polarization and dipole polarization, improves dielectric loss, and further produces a stronger electromagnetic wave loss capacity, thereby obtaining a relatively excellent electromagnetic shielding performance.
[0142] The CoFe@MXene / carbon aerogel composite material prepared by the method of the present invention has a unique design of the three-dimensional structure of the composite material and the effect of the magnetic component, which improves the impedance matching, makes it easier for electromagnetic waves to enter, and multiple reflections and scattering occur in the porous structure. The incident wave is attenuated by the magnetic loss of CoFe and the interface polarization and dipole polarization caused by a large number of effective interfaces, thereby obtaining excellent electromagnetic shielding performance. When the content of CoFe in MXene is 30wt% and the carbonization temperature is 1200℃, the electromagnetic shielding effectiveness of the prepared composite material is 75.5dB. This provides a feasible solution for making electromagnetic shielding materials with excellent electromagnetic shielding performance and electromagnetic wave absorption performance.
[0143] The preparation method of the CoFe@MXene / carbon aerogel composite material of the present invention utilizes a freeze-drying method, an in-situ synthesis method and a high-temperature carbonization process to prepare the CoFe@MXene / carbon aerogel composite material with high-efficiency electromagnetic shielding performance. The preparation process is safe and environmentally friendly, the preparation process is simple and the cost is low, and it has wide practicality and promotion value. The CoFe@MXene / carbon aerogel composite material prepared by the preparation method of the present invention has excellent electromagnetic shielding performance and can meet the application requirements of aerospace, electronic packaging and other fields.
Claims
1. A method for preparing a CoFe@MXene / carbon aerogel composite material, characterized in that: Follow the steps below to implement it: Step 1, preparing a few-layer MXene powder by etching Ti3AlC2 precursor with LiF-HCl; Step 2, preparing CoFe2O4@MXene powder by hydrothermal method; specifically, dissolving PVP in deionized water under magnetic stirring, adding Fe(NO3)3·9H2O, Co(NO3)2·6H2O and few-layer MXene powder to the solution after complete dissolution, ultrasonically dispersing for 30 minutes, adding urea, mixing evenly, then transferring the mixed solution to a high-pressure reactor, sealing, hydrothermally reacting at 180°C for 12 hours, naturally cooling to room temperature, collecting the precipitate, washing and drying, and obtaining CoFe2O4@MXene powder; The mass ratio of PVP, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, few-layer MXene powder, urea and deionized water is 0.15: 0.135~0.404: 0.097~0.145: 0.7047~0.548: 0.12: 60; Step 3, using CoFe2O4@MXene powder and cellulose to prepare CoFe2O4@MXene / cellulose aerogel; specifically: Step 3.1, add NaOH and urea to deionized water, stir for 15 minutes to obtain a mixed solution, and then place the mixed solution in a refrigerator for refrigeration; then add cellulose powder, stir evenly, freeze the solution in a refrigerator, thaw naturally, add CoFe2O4@MXene powder, disperse by ultrasonic, and then freeze at -26°C for 12 hours. After natural thawing, add MBA and stir evenly; Step 3.2, pour the mixed solution obtained in step 3.1 into a mold of a six-well cell culture plate, let it stand for one day to obtain CoFe2O4@MXene / cellulose hydrogel, then wash it with deionized water to neutrality, freeze it at -26°C for 12h, and finally freeze-dry it for 48h to obtain CoFe2O4@MXene / cellulose aerogel; Step 4, placing the CoFe2O4@MXene / cellulose aerogel obtained in step 3 into a tubular furnace for carbonization treatment to obtain a CoFe@MXene / carbon aerogel composite material.
2. The method for preparing the CoFe@MXene / carbon aerogel composite material according to claim 1, characterized in that: In step 1, the specific steps are as follows: Step 1.1, LiF and HCl are fully mixed, and then MAX phase precursor powder is slowly added under ice bath conditions to obtain a mixture; The mass ratio of LiF, HCl and MAX phase precursor powder is 1:20:1; Step 1.2, stirring the mixture at 35 °C for 24 h to obtain Ti3C2T x The suspension was then repeatedly centrifuged and washed with deionized water until the pH of the solution was 7 to obtain Ti3C2T x Sediment; Step 1.3, Ti3C2T x The precipitate was dispersed in deionized water and ultrasonically treated for 15 min to promote the delamination of multilayer MXene. Then, the mixture was centrifuged at 3500 r / min for 15 min, and the cycle was repeated several times. The supernatant was collected to obtain a few-layer MXene dispersion. Step 1.4, the few-layer MXene dispersion obtained above is pre-frozen at -26°C, and then freeze-dried using a freeze dryer to obtain a few-layer MXene powder.
3. The method for preparing the CoFe@MXene / carbon aerogel composite material according to claim 1, characterized in that: In the step 3.1, the refrigeration temperature is -12°C, and the refrigeration time is 12 hours; the freezing temperature is -26°C, and the freezing time is 24 hours.
4. The method for preparing the CoFe@MXene / carbon aerogel composite material according to claim 1, characterized in that: In the step 3.1, the mass ratio of NaOH, urea, CoFe2O4@MXene powder, cellulose powder, MBA and deionized water is 7:12:0.1458:2.43:2.34:
81.
5. The method for preparing the CoFe@MXene / carbon aerogel composite material according to claim 1, characterized in that: In step 4, the carbonization conditions are as follows: nitrogen is introduced at a rate of 50 to 100 mL / s, the temperature is first raised to 300° C. at a rate of 3° C. / min and kept for 1 hour, then the temperature is raised to 800° C. to 1200° C. at a rate of 5° C. / min and kept for 2 hours, and then cooled to room temperature.
Citation Information
Patent Citations
Aerogel fiber filling material as well as preparation method and application thereof
CN112813584A
Preparation method and application of graphene oxide and MXene co-doped cellulose-based carbon aerogel
CN112871135A
Preparation method of MXene-carbon aerogel / TPU composite material
CN112911920A